Analysis of an absorption cycle driven by temperature-distributed heat sources. (25th January 2019) - Xu, Qingyu; Lu, Ding; Chen, Gaofei; Guo, Hao; Dong, Xueqiang; Zhao, Yanxing; Shen, Jun; Gong, Maoqiong
Highlights: A new generator structure driven by temperature-distributed heat is proposed. Waste heat is utilized in a large temperature span with the new structure. The effects of different generator structures and heat distribution are studied. A composite criterion is proposed to evaluate the waste heat utilization. Abstract: An ammonia–water absorption refrigeration system with a novel generator structure driven by temperature-distributed heat sources to increase the utilization rate of waste heat is presented. The stripping section of the distillation column and generator were replaced by a generator with temperature-distributed heat sources. The heat sources were distributed throughout the entire process in the generator, so the mass and heat transfer were coupled at different temperatures, which increased the waste heat utilization at low temperatures. Compared with a traditional system, temperature–distributed heat sources increased the utilization temperature range. In the simulation of the system, the condition at cold end kept unchanged while the heating distributions and quantity inside the generator were changed. The performance of the new generator driven by temperature-distributed heat sources was analyzed while compared with a traditional system through the coefficient of performance, separation efficiency and waste heat utilization.